HUBUNGAN PENGUASAAN LAHAN DAN PENDAPATAN RUMAHTANGGA DI PEDESAAN (Kasus di Propinsi Jawa Tengah, Sumatera Barat dan Kalimantan Barat) - SUPRIYATI -; SAPTANA -; YANA SUPRIYATNA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
Historically correlation between landowner and land holding structure with householdincome structure in the rural area is linearity. Land owner or land holding structure inequalitymain factors to cause income structure inequality. In condition, there are the opportunityemploy and economic activity to open up, why is the correlation between landowner and landholding structure with the income structure? This paper objective to study: (1) Land owneror land holding structure in the rural area; (2) Household income structure in the rural area;and (3) The correlation between landowner and land holding structure with the householdincome structure in the rural area. Location on this study to focused in the three district inthree provincial exes. Klaten, central Java; Pasaman, West Sumatera; and Landak, WestKalimantan. The study to analyze by descriptive, gini index, and correlation analyze. Ingeneral, land owner and land holding size in Klaten, central Java less than West Sumatera andWest Kalimantan. Gini index analysis relatively to indicate high equality, except in Pasaman,West Sumatera. Inequality on land holding lower than landowner does in all location. Totalincome in Klaten, Central Java to range Rp. 6,77 - 6,97 million/years; Pasaman, WestSumatera to range Rp. 7,30 – Rp. 8,10 million/years; and in Landak, West Kalimantan torange Rp. 5,90 – 6,65 million/years. Analyze gini index for household income to indicatehigh inequality income structure rural area in Klaten. On the other hand, rural area inPasaman, West Sumatera and Landak, West Kalimantan gini index result reflecting lowinequality. There are deferent factors by location to cause inequality of landowner or landholding and household income structure, in Klaten rural area caused by high proportionincome source from non-agriculture. On the other hand, in Pasaman and Landak rural areacaused by level of technology adoption and kind of commodity planting by farmers.Statistically, correlation between landowner and land holding structure with householdagriculture income is not significant. Correlation between total income with the landowner orland holding in Pasaman, West Java is significant, but in Klaten, Central Java and Landak,West Java is not significant.